Dibutyl phthalate contamination remolded the fungal community in agro-environmental system. (January 2019) - Kong, Xiao; Jin, Decai; Wang, Xinxin; Zhang, Fengsong; Duan, Guilan; Liu, Huijun; Jia, Minghong; Deng, Ye
Abstract: Dibutyl phthalate (DBP) is a typical soil contaminant that is widely used as plasticizer in modern agricultural production. In this study, an experiment was conducted to evaluate fungal community succession in a soil-vegetable ecosystem under different DBP concentrations. By using high-throughput sequencing of the ribosomal internal transcribed spacer (ITS) region, it was shown that DBP contamination caused significant changes to the soil fungal community, in terms of both α and β diversities. The largest changes in fungal α and β diversities were detected under 50 mg/kg DBP concentration at the first day of addition. The bulk soils, rhizosphere soils and the phyllosphere harbored different fungal communities, while the abundance of saprotrophs and plant pathogens in the phyllosphere have been increased under DBP contamination. From correlation analysis and partial Mantel test, the change in fungal community α diversity was the result of multiple factors (DBP concentration, bacterial community and soil properties) while the β diversity of fungal community was mainly co-varied with the bacterial community after DBP contamination. Moreover, molecular ecological network analysis demonstrated that DBP contamination was detrimental to mutualistic relationships among fungal species and destabilized the network structure. Overall, the fungal communities in soils and around vegetables were largely remolded by DBP contamination that provides new insight into DBP contamination impacts on agricultural ecosystems. Highlights: DBP would change both α and β diversities of fungal community. The variation of fungal community were influenced by DBP pollution, bacterial community and soil properties. The molecular ecological network structure of fungal community was destabilized under DBP stress.